Educação musical para estudantes com deficiência visual mediada pela flauta doce - Almeida, Izabel Cristina Lopes de (2024)
This study presents a proposal for music education using the recorder for students with visual impairments (low vision and blindness). For this work, we chose three specific objectives: to identify the skills and competences that need to be worked on in flute teaching; to identify adaptations in the way of working and in the teaching material; and to reflect on the educational strategies and procedures used in teaching. The literature review presents the normative parameters on the teaching of Art and Music, and the process of including students with disabilities in Brazilian schools (Penna, 2014; Fonterrada, 2008; Bonilha, 2010; Juvêncio and Trompieri Filho, 2017; Tudissaki, 2014; Louro, Alonso and Andrade, 2006; Louro, 2015; Oliveira, 1997). The research was carried out in a state public school in the city of Fortaleza, during the second semester of 2023, in art classes, with students from the final years of elementary school. The dissertation used a qualitative methodology and an action research approach. The instruments used to collect data were focus groups and interviews with students with visual impairment and field diary entries made by the researcher. Data analysis used the triangulation technique. The research shows that everyone, regardless of their condition, has a guaranteed right to education and, consequently, to musical artistic knowledge. In the context of visually impaired students, teachers need to be aware of accessibility and inclusion resources, which favor the development of musical teaching and learning in an effective way, according to individual needs. The study made it possible to list the skills and abilities that need to be worked on when teaching the recorder (listening, perception and appreciation of sounds, recorder techniques and tactile perception, etc). We identified adaptations in teaching and learning materials for students with low vision (enlarged texts in ink, optical resources and information and communication technologies), and for blind students (transcription of scores and texts into Braille, screen readers and voice synthesizers). We believe that interventions through mediation and interactions with the environment can contribute to the development and musical knowledge of all individuals.